How can globalization affect inflation? Example of EMU countries - Milan Kostić; Marija Radulović (Cogent Social Sciences)
Globalization is a phenomenon researchers have paid great attention to in recent years. They estimated that globalization is a key structural dynamic that could keep inflation low, especially in developed economies. Therefore, the aim of the paper is to examine the impact of globalization, i.e. its dimensions (economic, social, and political), on inflation in EMU countries as developed economies. Researchers use data from 1970 to 2021. ARDL approach is used to test the short and long-run relationship between globalization and inflation. The results show an increasing effect of globalization on inflation in the short-run and a decreasing effect in the long-run. The short-run effect of economic globalization results from the harmonisation process, while the long-run effect results from stronger competition with more domestic and abroad enterprises. The conclusions could give good recommendations to the policymakers on explaining the effect of economic globalization (trade, FDI flows, portfolio investment, etc.) on inflation and which long-run benefits economic globalization and openness have on inflation.